Screening for delirium: a quality improvement audit in geriatric care - Jazba Yousaf; Shams Ud Duja; Areeba Asghar; Sami Mehdi; Faiza Khan (Clinical Medicine, 2025)
Background: Delirium is a fluctuating disturbance in mental status, characterised by confusion, disorientation and impaired attention. It disproportionately affects older adults, leading to prolonged hospitalisation, cognitive decline and increased mortality. Timely identification and intervention are essential in mitigating these risks. Despite national guidance from the National Institute for Health and Care Excellence (NICE) recommending routine delirium screening, adherence to these guidelines remains inconsistent.1 This audit aimed to assess compliance with delirium screening protocols in a geriatric care setting and identify barriers to effective screening, with a view to implementing improvements. Objectives: • Evaluate adherence to Trust guidelines, mandating delirium screening within 24 h of admission using structured tools, such as the Confusion Assessment Method (CAM) or the 4AT2;• Identify barriers to effective screening and propose actionable strategies to enhance adherence. Methods: A retrospective audit was conducted at a large NHS Trust between July and September 2024, reviewing the medical records of 278 patients admitted to the elderly care ward, of which 60 had a confirmed diagnosis of delirium. Data on delirium screening within the first 24 h of admission were extracted from the Sunrise Electronic Health Records system, and essential investigations, such as thyroid-stimulating hormone (TSH), vitamin B12, and folate levels were also reviewed.3 Results: The audit showed a steady improvement in delirium screening compliance: 19% (6/31) in the first cycle, 48% (15/31) in the second, and 55% (33/60) in the third (Fig 1). Despite this improvement, essential diagnostic investigations were often omitted. Notably, 93% of those with partial screening did not undergo TSH, B12, or folate testing, 41% lacked a chest X-ray, and 44% did not under an electrocardiograhy screen.4,5 These omissions suggest gaps in the diagnostic work-up, hindering accurate delirium management.6 Conclusions: The audit showed a significant increase in delirium screening compliance, from 19% to 55%. However, essential diagnostic tests were frequently omitted, delaying diagnosis and treatment. Early delirium identification is crucial to reduce hospital complications, improve recovery and prevent long-term cognitive decline. The audit emphasises the need for ongoing improvements in screening practices and integrating essential diagnostic tests [7]. Recommendations: 1. Staff education: ongoing training for healthcare professionals on delirium recognition and the use of structured screening tools (CAM, 4AT) should be prioritised to ensure staff competency8; 2. Electronic integration: integrating delirium screening tools into the electronic health record system will streamline screening and increase adherence to protocols9; 3. Multidisciplinary approach: strengthening collaboration among healthcare professionals, including doctors, nurses and therapists, as well as engaging family members, will improve delirium management and reduce risk10; 4. Regular audits: re-audits should be conducted every 6 months to monitor progress, identify barriers to screening and ensure continued adherence to delirium screening guidelines.1 Key points: • Early identification and intervention in delirium are crucial for reducing hospitalisation duration, preventing cognitive decline and improving patient outcomes; • Despite improvements, delirium screening compliance remains below target, with deficiencies in essential diagnostic investigations that need to be addressed; • Continuous staff education, tool integration and regular audits are essential for sustained improvement.